PENGARUH IKLIM ORGANISASI TERHADAP KOMITMEN KARYAWAN PADA ATM REGIONAL CENTER BNI 46 CABANG BOGOR - Rizman Rifqie; Fuji Kusumah (STIE Binaniaga, 2008)
Organizational Climate has a significant influence on attitude and behavior of members of the organizational for being able to provide stability and security for employees. With a good organizational climate means it can understand the things that happen in the environment of employees and find out how to overcome them.Environment organizations, environmental organizations both within and outside the organization environment will greatly affect the activities, norms, attitude, implementation of the role which can ultimately affect organizational commitment productivity and growthThe result of hypothesis testing are as follows: (1) Most of the employees at the ATM BNI Regional Center Bogor branch 46 when analyzed in carrying out their duties included in the category are committed in perfoming their duties, (2) statistical influence between employee commitment variables (Y) is indicated by the correlation coeficient (ry = 0.901), very meaningful (significant), positive affect. In a sense the higher the value of organizational climate variables then the higher the value of employee commitment (Y), or conversely, the lower the organizational climate, the lower value of employee commitment (3) Functional influence between organizational climate variables (X) with employee commitment variables (Y) is shown by a simple linear regression equation Y = 17.192 + 0.781 X, is mean and linear. Simple linear regression equation states that any increase in a score of organizational climate variable (X) will affect the rise i employees commitment variables (Y) of 0.781 on the constants of 17.192. So it can be concluded that organizational climate is an important factor to employee commitment, and chie square test asymp. Sig reference value. (2-sided) of 0.056> 0.05, it can be concluded that the mutual commitment and employee status is not free